CDP-choline is not protective in the SOD1-G93A mouse model of ALS. Issue 4 (1st May 2013) - Knippenberg, Sarah; Skripuletz, Thomas; Rath, Klaus Jan; Thau, Nadine; Gudi, Viktoria; Pul, Refik; Körner, Sonja; Dengler, Reinhard; Stangel, Martin; Petri, Susanne
Abstract: Important pathogenic factors in ALS include excitotoxicity and oxidative stress. Cytidine 5-diphosphocholine (CDP-choline) has recently been reported to have neuroprotective effects in animal models for neurodegenerative diseases, attributable to its anti-glutamatergic, anti-excitotoxic, anti-apoptotic and membrane-preserving properties. In this study we administered either CDP-choline or vehicle to transgenic SOD1-G93A mice daily via intraperitoneal (i.p.) injection starting before disease onset (day 30). By monitoring of survival, motor function, weight and general condition we examined possible therapeutic effects. Additional animals were used for histological studies to determine the effect of CDP-choline on motor neuron survival, astrocytosis and myelination in the spinal cord. Results showed that CDP-choline treatment modified neither the deterioration of general condition nor the loss of body weight. Survival of CDP-choline treated animals was not prolonged compared to vehicle treated controls. None of the behavioural motor function tests revealed differences between groups and no differences in motor neuron survival, astrocytosis or myelination were detected by histological analyses. In conclusion, our data from the transgenic mouse model do not strongly support further clinical validation of CDP-choline for the treatment of ALS.